2015
DOI: 10.1186/s13000-015-0264-6
|View full text |Cite
|
Sign up to set email alerts
|

Decreased functional activity of multidrug resistance protein in primary colorectal cancer

Abstract: BackgroundThe ATP-Binding Cassette (ABC)-transporter MultiDrug Resistance Protein 1 (MDR1) and Multidrug Resistance Related Protein 1 (MRP1) are expressed on the surface of enterocytes, which has led to the belief that these high capacity transporters are responsible for modulating chemosensitvity of colorectal cancer. Several immunohistochemistry and reverse transcription polymerase chain reaction (RT-PCR) studies have provided controversial results in regards to the expression levels of these two ABC-transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…However, the chemical efflux pump proteins, i.e. , the ATP-binding cassette (ABC) transporters, are ubiquitously expressed in enterocytes 3 , 4 , making it easier for CRC cells to develop chemotherapeutic multidrug resistance (MDR) for both conventional chemotherapeutics and the novel molecular-targeted chemicals 5 . Owing to the differences in cell entry and action mechanisms, macromolecular proteins such as anti-EGFR monoclonal antibody can bypass the MDR pathway for small chemical drugs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the chemical efflux pump proteins, i.e. , the ATP-binding cassette (ABC) transporters, are ubiquitously expressed in enterocytes 3 , 4 , making it easier for CRC cells to develop chemotherapeutic multidrug resistance (MDR) for both conventional chemotherapeutics and the novel molecular-targeted chemicals 5 . Owing to the differences in cell entry and action mechanisms, macromolecular proteins such as anti-EGFR monoclonal antibody can bypass the MDR pathway for small chemical drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ji et al (9) reported elevated MRP1 expression in CRC tissues, and identified a significant correlation between MRP1 expression and Dukes' stage, in addition to poor patient prognosis. Micsik et al (11) suggested that MDR activity may be associated with acquired chemoresistance in CRC. Furthermore, another study suggested that MRP1 inhibition was involved in the fingolimod-induced chemosensitization of HCT-8/5-FU cells (10).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies identified no association between MRP1 expression and CRC-associated MDR (5-7). However, other studies identified high expression levels of MRP1 in CRC cells and produced results that indicated that there was a significant correlation between MRP1 expression and tumor stage/poor patient prognosis, in addition to an association with acquired chemoresistance, in CRC (8)(9)(10)(11). The results of a study performed by Xing et al (10) suggest that MRP1 expression is not correlated with the functional changes of MRP1 transporters, which may partially explain the inconsistency in the results of the studies discussed above.…”
Section: Introductionmentioning
confidence: 98%
“…They found a correlation between the expression of BCRP and MRP1 and clinical outcome in the patients treated with anthracycline‐based chemotherapy. Regarding colorectal cancer, Micsik et al, measured functional activity of MDR1 and MRP1 by modified calcein‐assay in primary colorectal tumors and compared to normal mucosa. They found no difference in MRP1 activity between these sites.…”
Section: Discussionmentioning
confidence: 99%